2018
DOI: 10.1080/03639045.2018.1542708
|View full text |Cite
|
Sign up to set email alerts
|

Oral delivery of the anti-tumor necrosis factor α domain antibody, V565, results in high intestinal and fecal concentrations with minimal systemic exposure in cynomolgus monkeys

Abstract: Objective: V565 is a novel oral anti-tumor necrosis factor (TNF)-a domain antibody being developed for topical treatment of inflammatory bowel disease (IBD) patients. Protein engineering rendered the molecule resistant to intestinal proteases. Here we investigate the formulation of V565 required to provide gastro-protection and enable optimal delivery to the lower intestinal tract in monkeys. Methods: Enteric-coated V565 mini-tablets were prepared and dissolution characteristics tested in vitro. Oral dosing of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…This tablet exhibited the sustained drug release at pH ≥ 6 but no drug release during 2-hr incubation in acidic conditions. In vivo studies in monkeys also supported the sustained release of V565 in the intestine for the topical treatment of IBD [44]. In addition, the drug release profiles can be manipulated by using a combination of copolymers with varying the ratios [44].…”
Section: Tablets and Capsulesmentioning
confidence: 88%
See 2 more Smart Citations
“…This tablet exhibited the sustained drug release at pH ≥ 6 but no drug release during 2-hr incubation in acidic conditions. In vivo studies in monkeys also supported the sustained release of V565 in the intestine for the topical treatment of IBD [44]. In addition, the drug release profiles can be manipulated by using a combination of copolymers with varying the ratios [44].…”
Section: Tablets and Capsulesmentioning
confidence: 88%
“…In vivo studies in monkeys also supported the sustained release of V565 in the intestine for the topical treatment of IBD [44]. In addition, the drug release profiles can be manipulated by using a combination of copolymers with varying the ratios [44]. This combination system may be superior to tablets coated with a single polymer for colon-targeted drug delivery.…”
Section: Tablets and Capsulesmentioning
confidence: 92%
See 1 more Smart Citation
“…24 Clinical anti-TNF-α treatment can effectively improve intestinal barrier function and ameliorate IBD symptoms. 25,26 In our in vitro study, we used Treg-Exo to culture with colonic epithelial YAMC cells in the presence of TNF-α to investigate the communication between Tregs and intestinal epithelial cells. We found that Treg-Exo could be transferred to YAMC cells where Treg-Exo promoted cell proliferation and inhibited cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TIBC refers to serum transferrin‐binding iron, and the value of which can indirectly reflect the transferrin content, further proves that the iron supplementation of enteric‐coated Fe‐Gly(1:1) and enteric‐coated Fe‐Gly(2:1) is better than uncoated iron supplements. Some scholars have found that IB‐CP SRCs can maintain the effective blood concentration of the body for a long time by comparing the ibuprofen enteric‐coated sustained‐release pellets (IB‐SRPs) with conventional tablets (Huang, Lu, Li, Luo, & Liu, ); Crowe et al found that the drug passed after the enteric coating, the drug can be released in a specific part of the monkey (intestine) to improve the utilization of the drug; meanwhile (Crowe et al, ); Xu et al also believe that enteric coating treatment can be used as an effective carrier for oral drugs (Xu et al, ).…”
Section: Discussionmentioning
confidence: 99%